Band gap engineering of Si-Ge alloys for mid-temperature thermoelectric applications - J. J. Pulikkotil; S. Auluck (AIP Advances, 2015)
The viability of Si-Ge alloys in thermoelectric applications lies in its high figure-of-merit, non-toxicity and earth-abundance. However, what restricts its wider acceptance is its operation temperature (above 1000 K) which is primarily due to its electronic band gap. By means of density functional theory calculations, we propose that iso-electronic Sn substitutions in Si-Ge can not only lower its operation to mid-temperature range but also deliver a high thermoelectric performance. While calculations find a near invariance in the magnitude of thermopower, empirical models indicate that the materials thermal conductivity would also reduce, thereby substantiating that Si-Ge-Sn alloys are promising mid-temperature thermoelectrics.